Jorge Ferreira de Vasconcelos: a comédia, a cidade e a corte - Marnoto, Rita (2018)
(2018). Jorge Ferreira de Vasconcelos: a Jorge Ferreira de Vasconcelos, a cidade e a corte, Limite, 12, 1: 29-43. ISSN 1888 4067